Harry Potter and the Order of the Phoenix - Barron, David; Heyman, David, 1961-; Goldenberg, Michael; Yates, David, 1963-; Radcliffe, Daniel, 1989-; Watson, Emma, 1990-; Grint, Rupert, 1988-; Smith, Maggie, 1934-; Thompson, Emma.; Fiennes, Ralph; Rickman, Alan.; Oldman, Gary.; et al. (Burbank, CA : Warner Home Video, 2007)
Lord Voldemort has returned, but the ministry of Magic is doing everything it can to keep the wizarding world from knowing the truth. They appoint Ministry official Dolores Umbridge as the new Defense Against the Dark Arts professor at Hogwarts. When Umbridge refuses to teach practical defensive magic, Ron and Hermione convince Harry to secretly train a select group of students for the wizarding war that lies ahead. A terrifying showdown between good and evil awaits.
Title from container.
Based on the novel by J.K. Rowling.
Director of photography, Slawomir Idziak ; editor, Mark Day ; music, Nicholas Hooper ; costume designer, Jany Temime ; production designer, Stuart Craig ; special effects supervisor, John Richardson ; visual effects supervisors, Tim Burke, Craig Lyn, Chris Shaw.
Daniel Radcliffe, Emma Watson, Rupert Grint, Maggie Smith, Emma Thompson, Ralph Fiennes, Alan Rickman, Gary Oldman, Helena Bonham Carter, Imelda Staunton.
MPAA rating: PG-13; for sequences of fantasy violence and frightening images.
DVD, region 1, widescreen (2.40:1) presentation; Dolby Digital 5.1 surround, DVD-9.
Keywords: Potter, Harry (Fictitious character) -- Drama; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Drama; Wizards -- Drama; Good and evil -- Drama; Defensive (Military science) -- Drama; Wizards -- Drama; Brujera̕ -- Teatro; Bien y mal -- Teatro; Potter, Harry (Fictitious character) -- Drama; Hogwarts School of Witchcraft and Wizardry (Imaginary place) -- Drama; Good and evil -- Drama; Defensive (Military science) -- Drama; Feature films; Fantasy films; Action and adventure films; Films for the hearing impaired; Feature films; Action and adventure films; Fantasy -- Feature; Fantasy films